Reducing pollutant emissions from a heavy-duty diesel engine by using hydrogen additions. (15th May 2016) - Jhang, Syu-Ruei; Chen, Kang-Shin; Lin, Sheng-Lun; Lin, Yuan-Chung; Cheng, Way Lee
Highlights: The hydrogen supplement enhances diesel engine thermal efficiency. The hydrogen produced from water electrolysis can reduce the fuel consumption. H2 addition reduces the traditional pollutants at idling condition. A great improvement on CO, CO2 emissions was observed with hydrogen addition. An important reduction on NOx was achieved with H2 addition at low loads. Abstract: This study aimed to investigate the effect of conventional diesel engine through the addition of H2 mixture, generated through water electrolysis. In this work, three different ratios of diesel–hydrogen blends, 0%, 0.6% and 1.2% hydrogen by volume used, respectively. The experiments were carried out at the idling condition under constant speed from the low to high engine load with the different amount of H2 mixture. The results showed that the brake thermal efficiency (BTE) increased as the brake specific fuel consumption (BSFC) decreased with an increasing amount of hydrogen. The hydrogen addition leads to reduce the emissions of carbon dioxide (CO2 ) and carbon monoxide (CO). At the high operation load, the reduction in emissions was the most significant, but the total hydrocarbon (THC) emissions increased 4.94% and 13.1% on average with the low level of hydrogen addition (0.6% and 1.2% by volume). Nevertheless, the addition of hydrogen lowered nitrogen oxide (NOx) emissions at the idling and low load conditions, but increased at the high load, since the thermal NOx dominated at the higher temperature. Consequently, the addition of low level hydrogen decreased CO and CO2 emissions, whereas the THC and NOx emissions increased at the high engine load.